(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
It is important to instill student character education in every educational institution from an early age because character education has the same essence and meaning as moral education. The aim of this research is, among other things, to describe the implementation of religious, disciplined and independent character education at Al Badar Kindergarten. The research approach used in this research is a qualitative research method. Research findings show that the implementation of character formation in young students with religious, disciplined and independent elements at Al Badar Tulungagung Kindergarten is carried out through stages, program planning, integration processes, character formation and evaluation. The process of character learning in religious elements includes the habit of saying greetings, praying, praying in congregation, reading the Qur’an, and memorizing. The process of character learning in the discipline element includes time discipline and attitude discipline. The process of learning character education in the independent element is carried out by getting used to going to school alone, studying in your own class, doing your own activities, and solving your own problems. The process of learning character education in the independent element is carried out by getting used to going to school alone, studying in your own class, doing your own activities, and solving your own problems.